Judge Al Villa Swears In New Attorney Cristobal Perez - Watkins, Howard::::::::: (1983)
Administration of oath; Howard Watkins, Alice Gutierrez, Doris Burnes, Ruben Lucero, Virginia Salmeron, Gloria Escalante, Judge Al Villa, Cristobal Perez, Betsy Temple, Charles Kahill, Aggie Rose, Elaine Harris; viewed from judge's bench